Vegetation characteristics and lesser prairie chicken responses to land cover types and grazing management in western Kansas - Kraft, John Daniel (Kansas State University, 2016)
In the southern Great Plains, the lesser prairie-chicken (Tympanuchus pallidicinctus; hereafter LEPC), an obligate grassland species, has experienced significant population declines and range contractions with subsequent conservation concern. Management actions often use land cover types to make inference about habitat quality. Relatively little information is available related to grazed rangelands to guide conservation. The influences of land cover types and livestock grazing on LEPC habitat selection have not been researched extensively in western Kansas. I evaluated the influence of land cover types and grazing management on vegetation characteristics, habitat selection, and nest/adult survival of LEPC in western Kansas. Females were captured and radio-marked to monitor habitat use, nest success, and adult survival. Grazing and vegetation data were collected via producer correspondence and vegetation surveys, respectively. Vegetation composition and structure differed across land cover types, which can be used to make inferences about LEPC habitat quality. Habitat selection analyses corroborated the importance of breeding habitat in close proximity to leks (<3 km) and identified land cover types selected for nesting (Conservation Reserve Program, Limy Upland, Saline Subirrigated) and brooding (Conservation Reserve Program, Red Clay Prairie, Sands, Sandy Lowland). Conservation Reserve Program patches positioned near rangelands contributed to LEPC reproductive success in northwest Kansas. In grazed lands, LEPC selected habitat close to leks (<3 km) and large pastures (>400 ha), exhibiting low-moderate stocking densities (<0.4 AU/ha), and low-moderate levels of deferment during the grazing season (60-100 days). Nest site selection was negatively influenced by increasing distance from a lek and grazing pressure. Daily nest survival rates were negatively influenced by increasing grazing pressure and high levels of stocking density. Annual adult female survival was negatively influenced as forage utilization (% forage removed) increased. Heterogeneity (coefficient of variation and standard deviation) of visual obstruction was decreased at stocking densities > 0.26 AU/ha. Future conservation actions should consider the potential of land cover types to create adequate vegetation structure, and manage rangelands with low-moderate stocking densities and deferment and greater pasture areas. The relationship between habitat selection and proximity of lek sites (< 5 km) should be used to identify quality LEPC habitat.
Keywords: Lesser prairie-chicken; Grazing; Habitat selection; Ecological sites